Réponses

Meilleure réponse !
2014-01-15T16:06:18+01:00
A = (x+1)(2+x)
   = 2x + x² + 2 + x
A = x² + 3x + 2
   
B = (2+x)(5+x)
   = 10 + 2x + 5x + x²
B = x² + 7x + 10

C = (2x+7)(3x+4)
   = 6x
² + 8x + 21x + 28
C = 6x² + 29x + 28
 
D = (6+9x)(7x+8)
   = 42x + 48 + 63x² + 72x
D = 63x² + 114x + 48
2014-01-15T16:10:20+01:00
a. 
(x+1)(2+x)
=x*2+x*x+1*2+1*x
=2x+1x²+2+1x
=1x²+3x+2

b. 
(2+x)(5+x)
=2*5+2*x+x*5+x*x
=10+2x+5x+1x²
=1x²+7x+10

c.
(2x+7)(3x+4)
=2x*3x+2x*4+7*3x+7*4
=6x²+8x+21x+28
=6x²+29x+28

d.
(6+9x)(7x+8)
=6*7x+6*8+9x*7x+9x*8
=42x+48+63x²+72x
=63x²+114x+48

p-s: * c'est le fois

voilà :)